2018
DOI: 10.3855/jidc.9653
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adherence to tuberculosis treatment in Iranian patients: Application of health belief model

Abstract: Introduction: Adherence to TB treatment is an important issue for TB control, with key health consequences. Identification of the factors associated with that adherence is also important. The objective of this study was to identify factors associated with adherence to tuberculosis treatment, using the health belief model (HBM). Methodology: Overall 297 TB patients were recruited to the study using the census method. All patients completed a 40-question survey form anonymously. The questionnaire was devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 25 publications
(30 reference statements)
2
19
0
Order By: Relevance
“…The HBM is framed on a number of key health beliefs, such as perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and self-efficacy that persuade individuals to make healthy behavior changes. The HBM has been used in previous studies to characterize response to health threats such as the swine flu, tuberculosis, and others [41][42][43][44]. Based on the framework, smokers who perceive themselves susceptible to a threat are more likely to engage in reduction or quitting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The HBM is framed on a number of key health beliefs, such as perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and self-efficacy that persuade individuals to make healthy behavior changes. The HBM has been used in previous studies to characterize response to health threats such as the swine flu, tuberculosis, and others [41][42][43][44]. Based on the framework, smokers who perceive themselves susceptible to a threat are more likely to engage in reduction or quitting behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…This study explored challenges faced by parents in two districts of an urbanised state in Malaysia according to the HBM construct of perceived barriers [31]. HBM explained a theory exploring community behaviour on a disease prevention activities which also includes other constructs such as perceived susceptibility, perceived severity, self-efficacy, perceived benefits and cues to action [32].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed mother’s perceived threat towards obesity was a significant factor in predicting for child’s BMI. The study of Azizi et al [35] in tuberculosis patients revealed that effective threat perceptions are related to health decision-making. Similarly, Moore et al [13] indicated that perceived threat could create motivation for losing weight and having more physical activity.…”
Section: Discussionmentioning
confidence: 99%